A Critique of Consumer Culture and Millennial Catastrophe In Martin Amis’s London Fields (1989) - Zhaneen Arif Rushdi; Juan Abdullah Ibrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This scholarly and communal study investigates the design and notion of criticism in a modern culture inside the millennial catastrophe in the Social Satire London Fields (1989) of Martin Amis. The fiction is preferred due that it combines the features of how consumer culture is designed and settled in the society. The Context of the fiction is grown into the reality of which the culture and tradition of consumer and consumerism is at its peak and it appeals to the connection which the fictional work engages with readers and what perspectives are shown. Amis’s dark comedy, the London Fields is selected to be studied according to its academic articles and its public visibility in the society. London Fields abstracts the consumer culture and consumerism in an idea that it has shaped public perception and how as a literary text fictionalises consumerism as its main topic and the paper evaluates the subject matter emphasis as well. This paper critically discovers consumerism and consumer culture in the minds of the greedy individual and how it has become a main topic of Martin Amis’s fiction. Hence, the researcher seeks to analyse how London Fields depict the effects of consumer culture and consumerism and why Martin Amis is right in concentrating on the experience of fictional figures who are involved by consumerism, consumer culture and a millennial catastrophe. It indicates that consumer culture is a fundamental field to study and publish articles as it has become an attractive and proper issue of today’s world of globalisation, capitalism, and the socio-cultural pages of history of our current time. Adding this, the main themes that Martin Amis utilises in his novel and the process he fictionalises his story are related depictions of characters dominated by consumerism that aid readers a social, cultural and academic function to a concise conclusion and analysis.